Putusan Perkara Tindak Pidana Korupsi Dalam Kasus PT Asuransi Jiwasraya Dan PT ASABRI - Julianti, Angelia Lyshandra; Hehanussa, Deassy Jacomina Anthoneta; Hattu, Jacob (MATAKAO Corruption Law Review, 2024)
Introduction: The crime of corruption is one of the extraordinary crimes which in it’s implementation can harm state finances. As stipulated in the provisions of Law Number 31 of 1999, as amended by Law Number 20 of 2001 concerning the Eradication of Corruption. In violation of the crime of corruption, the perpetrator will be sentenced to punishment or sanctions in accordance with the provisions stipulated in the legislation Purposes of the Research: to find out whether the granting of a null verdict in the case of corruption No. 50/Pid.Sus-TPK/2021/PN Jkt.Pst is in accordance with the provisions of laws and regulations in Indonesia and 2. What are the legal consequences if the defendant is unable to pay compensation in a case of corruption at PT Asuransi Jiwasraya? Methods of the Research: The research method used is normative judicial research method using Statutory Approach, Conceptual Approach and Case Approach. Results of the Research: Based on the results of the research, it shows that the granting of zero verdicts in corruption cases is not in accordance with the regulations of Article 10 of the Criminal Code and the types of judges decisions, which do not contain an explanation of the zero verdict. The legal consequences if the defendant is unable to pay restitution in a corruption case at PT Asuransi Jiwasraya are regulated in Article 19 paragraph (1) letter b of the TIPIKOR Law. However, in this case the imposition of a fine is very ineffective because the defendant has received life imprisonment. Based on Article 67 of the Criminal Code, if the judges gives a criminal sentence, the legal consequences will be contrary to this article. The prosecutor can forcibly seize the defendant’s assets to be auctioned as a substitute for state losses and can file a civil lawsuit related to the return of state finances.